Nanoprobes‐Assisted Multichannel NIR‐II Fluorescence Imaging‐Guided Resection and Photothermal Ablation of Lymph Nodes. Issue 9 (15th February 2021) - Fan, Xiaoxiao; Li, Yirun; Feng, Zhe; Chen, Guoqiao; Zhou, Jing; He, Mubin; Wu, Lan; Li, Shengliang; Qian, Jun; Lin, Hui
Abstract: Lymph node metastasis is a major metastatic route of cancer and significantly influences the prognosis of cancer patients. Radical lymphadenectomy is crucial for a successful surgery. However, iatrogenic normal organ injury during lymphadenectomy is a troublesome complication. Here, this paper reports a kind of organic nanoprobes (IDSe‐IC2F nanoparticles (NPs)) with excellent second near‐infrared (NIR‐II) fluorescence and photothermal properties. IDSe‐IC2F NPs can effectively label lymph nodes and helped achieve high‐contrast lymphatic imaging. More importantly, by jointly using IDSe‐IC2F nanoparticles and other kinds of nanoparticles with different excitation/emission properties, a multichannel NIR‐II fluorescence imaging modality and imaging‐guided lymphadenectomy is proposed. With the help of this navigation system, the iatrogenic injury can be largely avoided. In addition, NIR‐II fluorescence imaging‐guided photothermal treatment ("hot" strategy) can ablate those metastatic lymph nodes which are difficult to deal with during resection ("cold" strategy). Nanoprobes‐assisted and multichannel NIR‐II fluorescence imaging‐guided "cold" and "hot" treatment strategy provides a general new basis for the future precision surgery. Abstract : A novel kind of second near‐infrared (NIR‐II) fluorescent nanoprobe is synthesized to label and trace lymph nodes (LNs). Together with other kinds of NIR‐II fluorescent NPs with different optical features, multichannel fluorescence imaging‐guided surgeries are successfully conducted. Photothermal ablation of metastatic LNs is introduced as a good complement to surgery. This platform offers a novel perspective through which a more precise surgery can be conducted.